Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1 ) ( 2x - 15 ) + 17 = 6
=> 2x - 15 = 6 - 17
=> 2x - 15 = - 11
=> 2x = - 11 + 15
=> 2x = 4
=> x = 4: 2
=> x = 2
Vậy x = 2
2) 15 - ( 4 - 3x ) = -4
=> 4 - 3x = 15 - ( -4 )
=> 4 - 3x = 19
=> 3x = 4 - 19
=> 3x = -15
=> x = -15 : 3
=> x = -5
Vậy x = -5
3) -21 + 3 . ( -x + 7 ) = - 18
=> 3 . ( -x + 7 ) = ( -18 ) - ( -21 )
=> 3 . ( -x + 7 ) = 3
=> -x +7 = 3 : 3
=> -x + 7 = 1
=> -x = 1 - 7
=> -x = - 6
=> x = - (- 6 )
Vậy x = - ( -6 )
4 ) 78 : ( 3x - 2 ) = -3
=> 3x - 2 = 78 : ( -3)
=> 3x - 2 = -26
=> 3x = -26 + 2
=> 3x = -24
=> x = -24 : 3
=> x = -8
Vậy x = -8
5) -35 : 5 . ( -3 - 2x ) = 35
=> -7 . ( -3 ) + 2x = 35
=> -3 + 2x = 35 : ( -7)
=> -3 + 2x = -5
=> 2x = (-5) - (-3)
=> 2x = -2
=> x = -2 : 2
=> x = -
Vậy x = -1
~ Chúc bạn học tốt ~
1/ (2x – 15) + 17 = 6
<=> 2x=4
<=> x=2
2/ 15 – (4 – 3x) = - 4
<=> 3x=-15
<=> x=-5
3/ - 21 + 3(-x + 7) = -18
<=> -3x=-18
<=> x=6
4/ 78 : (3x – 2) = -3
<=> 3x-2=-26
<=> 3x=-24
<=> x=-8
5/ -35 : 5.(-3 – 2x) = 35
<=> -3-2x=-7
<=> 2x=4
<=> x=2
Tìm số nguyên x, biết:
1) -16 + 23 + x = - 16
7+x=-16
x=-16-7
x=-23
2) 2x – 35 = 15
2x=15+35
2x=50
x=50:2
x=25
3) 3x + 17 = 12
3x=12-17
3x=-5
x=-5/3
4) (2x – 5) + 17 = 6
2x-5=6-17
2x-5=-11
2x=-11+5
2x=-6
x=-6:2
x=-3
5) 10 – 2(4 – 3x) = -4
2(4-3x)=10-(-4)
2(4-3x)=14
4-3x=14:2
4-3x=7
3x=4-7
3x=-3
x=-3:3
x=-1
6) - 12 + 3(-x + 7) = -18
3(-x+7)=-18-(-12)
3(x+7)=-6
x+7=-6:3
x+7=-2
x=-2-7
x=-9
(x+3).(2x-18)=0
=>x+3=0 hoặc 2x-18 =0
+)x+3=0
x=-3
+)2x-18=0
2x =18
x =9
Vậy x \(\in\)\(_{\left\{-3;9\right\}}\)
a)5-2x=3x+20
5=3x+20+2x
5=5x+20
=>5x+20=5
5x=5-20
5x=-15
x=(-15):5
x=-3
\(a.2x+35=x-27\)
\(\Leftrightarrow2x-x=-27-35\)
\(\Rightarrow x=-62\). Vậy \(x=-62\)
\(b.2x-41=3x+\left(-23\right)\)
\(\Leftrightarrow2x-3x=-23+41\)
\(\Leftrightarrow-x=18\)
\(\Rightarrow x=-18\). Vậy \(x=-18\)
\(c.4\left(x-3\right)-3\left(x+5\right)=45.\left(-2\right)-34\)
\(\Leftrightarrow4x-12-3x-15=-124\)
\(\Leftrightarrow4x-3x=-124+12+15\)
\(\Rightarrow x=-97\). Vậy \(x=-97\)
\(d.\left(x+3\right)\left(2x-18\right)=0\)
\(\Leftrightarrow\hept{\begin{cases}x+3=0\\2x-18=0\end{cases}\Rightarrow\hept{\begin{cases}x=-3\\x=9\end{cases}}}\). Vậy \(x=-3;9\)
2 ( 3x - 4 ) - ( 2x - 5 ) = -35
6x - 8 - 2x + 5 = -35
6x - 2x = -35 - 5 + 8
4x = -32
x = -8
Vậy x = -8
\(2\left(3x-4\right)-\left(2x-5\right)=-35\)
\(6x-8-2x-5=-35\)
\(4x-8-5=-35\)
\(4x-8=-35+5\)
\(4x-8=-30\)
\(4x=-30+8\)
\(4x=22\)
\(x=22:4\)
\(x=\frac{22}{4}\)
\(x=\frac{11}{2}\)